Perception of quality of life towards diabetes from Gender perspective - MANOJ ABRAHAM M (International Journal of Pharma and Bio Sciences, 2017)
The aim of this study was to investigate the perception of quality of life (QOL) towards diabetes from gender perspective. A cross-sectional study was carried out at Malaysia Diabetes Association, study included 100 participants they were divided based on gender, each with 50 subjects. They were given a demographic questionnaire and Ferrans and Power Index Diabetes Version III. The overall score for quality of life was higher in men compared to women with a p value of 0.006. Next in the score for health and function, men had higher scores than women with a p value of 0.028. Score in the socioeconomic perspective also showed that men have higher score compared to women with a p value of 0.030. The only score that is higher in women is the score under spiritual category. Women had a scored 17.57±2.20 compared to men 16.05±1.41. Score under family subscale showed lower values in men 15.09±1.28 than women 15.38±1.20. This finding indicated that male had better perception of quality of life compared to female.